Relevansi nilai-nilai piagam madinah terhadap pembentukan sikap toleransi siswa man 1 jembrana - Munirah, Munirah (Maliki Interdisciplinary Journal, 2026)
This study seeks to explore how the values of the Charter of Medina remain meaningful in shaping students’ attitudes of tolerance at MAN 1 Jembrana. The Charter of Medina—recognized as the first social constitution established by the Prophet Muhammad (peace be upon him)—embodies principles of justice, solidarity, protection of human rights, and respect for religious freedom. These values are not only historically significant but also deeply relevant to today’s educational landscape, especially within learning environments that are socially and religiously diverse, such as MAN 1 Jembrana. Using a qualitative library research approach, this study draws upon classical and contemporary literature on the Charter of Medina and moral education theories. The findings reveal that the values contained in the Charter offer meaningful guidance for nurturing tolerance among students. These values can be integrated through Islamic Cultural History (SKI) learning, the everyday culture of the madrasah, the example set by teachers, and students’ interactions with the surrounding community. Furthermore, theories of moral development and social learning suggest that students learn to become tolerant through understanding history, internalizing meaningful values, and practicing these values in daily life. In this way, the Charter of Medina is not merely a historical text—it becomes a living source of inspiration and a compassionate pedagogical foundation for fostering a spirit of tolerance within Islamic educational settings, particularly at MAN 1 Jembrana.